2016
DOI: 10.1177/2373379916639066
|View full text |Cite
|
Sign up to set email alerts
|

Photovoice as Pedagogy for Authentic Learning

Abstract: Students preparing for helping professions who understand the influences of income on health are better equipped to address health challenges in communities and in their future careers. Universities have a responsibility to bolster and provide a safe environment for students to build and practice their 21 st -century skills. When implemented as a pedagogical tool, photovoice projects have the potential to provide authentic learning experiences for students to engage in advocacy and civil discourse. Undergradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It provided a meaningful way to conclude the program by displaying photovoice projects at the CRFT graduation for fellows’ friends and families to see their work. We recommend also displaying the photovoice projects at community events to encourage further interaction with other community members around relevant topics (Massengale et al, 2016). Displaying the photovoice projects was also great marketing for the program as it expressed fellows’ enthusiasm and demonstrated their increased knowledge in public health methods.…”
Section: Discussion Conclusion and Lessons Learnedmentioning
confidence: 99%
See 2 more Smart Citations
“…It provided a meaningful way to conclude the program by displaying photovoice projects at the CRFT graduation for fellows’ friends and families to see their work. We recommend also displaying the photovoice projects at community events to encourage further interaction with other community members around relevant topics (Massengale et al, 2016). Displaying the photovoice projects was also great marketing for the program as it expressed fellows’ enthusiasm and demonstrated their increased knowledge in public health methods.…”
Section: Discussion Conclusion and Lessons Learnedmentioning
confidence: 99%
“…Gutierrez and Wolff (2017) found that using photovoice in an undergraduate health science course improved students' understanding of health disparities and even led some students to take action within their communities. Similarly, Massengale et al (2016) showed that integrating photovoice into an undergraduate course not only improved understanding of health outcomes among disadvantaged groups but also promoted advocacy and engagement in civil discourse. Furthermore, they show how organizing a community exhibit and displaying student photovoice projects increased awareness among community members in attendance around community health concerns.…”
Section: Cbpr Methods To Train and Engage Community Residentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2016 European essay focused on investigating the contributions of Photovoice to education; based on its conclusion, this method has benefits such as access to settings and subjective experiences that are harder to be understood through retrospective or observational research; student engagement to research process; real academic experiences; and reflection on teaching and learning processes 22 .…”
Section: Methodological Pathmentioning
confidence: 99%
“…In this issue of Pedagogy in Health Promotion is a set of experiential learning ideas for a range of formal learners from undergraduates, to MPH, to doctoral students. Massengale, Strack, Orsini, and Herget (2016) implemented a photovoice project for undergraduates to give them an authentic learning experience to help them engage in advocacy and civil discourse related to the health of low-income residents in a community. An added step in their work was to have residents of the community under observation review the students’ work and give feedback to the students.…”
mentioning
confidence: 99%